(3bdGFO GdfMhQ aj GdCHjGJ GdChd ef GdTPhQs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3GHf GQaY QGSg GdCfOdSj GdLjGfj, GHf GQaY QGSg GdCfOdSj GdLjGfj,J (B593 (3g` s ((3eOjfI gQGI s)
(3ChdgG (B:s
(3HYO GdHSedI hPcQ GdeDda(B: (3deG enf Gddg JYGdi Ydi hLYdfi eef jMH GdMceI hCgdgG hfXQJ ai cJH GdMceGA GdeJbOejf hGdeJBNQjf s
(3BNQgG (B:s
(3hCMeO Gddg MeOkG eJhGJQkG cKjQkG hCSCdg GdYah hGdEMSGf hGdaVd Efg gh GdefGf s
(3ai MQa GdCdas
(3fSNI cJHJ ef NW GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdcjejGA h GdWHjYjGJs